UPAYA MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) BERKARAKTER MELALUI SUPERVISI AKADEMIK DI SMK N 3 PATI - Sunoto Sunoto (Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kabupaten Pati, 2018)
ENGLISHThe background of this research is lower competency of teacher in SMK Negeri 3 Pati in preparing lesson plans character. Academic supervisions in SMK Negeri 3 Pati are conducted in order to improve the competency of teacher in preparing lesson plans character. The research subjects are the Islamic education teacher of grade X, the social science teacher of grade XII, the civic education teacher of grade X, the Indonesian language teacher of grade XI and the English language teacher of grade XI. This research method is descriptive with quantitative and qualitative approaches. The data are collected through documentation, observation, interviews and assignments. The research is designed through two cycles with procedure: (1) planning; (2) the action executions; (3) observation; and (4) reflection. The result shows that teacher’s competency increases indicated by: 1) the average score for the first cycle is 71 rated